Cultura e identidade híbrida na obra do artista plástico roraimense Jorge Augusto Cardoso - Rangel, Adriana Moreno (2012)
This paper discusses Roraima`s culture and identity and some developments from the hybridization process represented in the art work of the artist, Jorge Augusto Cardoso. For this purpose, we used theoretical and methodological foundations from Cultural Studies to cover Culture, Identity, Visual Language, Regional Art, Regionalism, Regionality, Hybridization and Representation in order to analyze the process of identity formation of Roraima, and to understand its elements involved in this process, which allowed us to view the forms of "being" Roraima, revealed in the artist imagery scenery, riddled by conflicts and differences. In this light, various forms of symbolic representations valued in the region, created by artist, were studied, and new concepts were extracted at the same time generating new readings. Thus, this analysis gives possibilities of identity developed in the system of representation contained in the work, in which spaces were designed and built, enabling subjects to position themselves and to build new identities; to appropriate and to reconstruct identities for their use.